2022
DOI: 10.1186/s13045-022-01311-6
|View full text |Cite
|
Sign up to set email alerts
|

Emerging strategies to overcome resistance to third-generation EGFR inhibitors

Abstract: Epidermal growth factor receptor (EGFR), the receptor for members of the epidermal growth factor family, regulates cell proliferation and signal transduction; moreover, EGFR is related to the inhibition of tumor cell proliferation, angiogenesis, invasion, metastasis, and apoptosis. Therefore, EGFR has become an important target for the treatment of cancer, including non-small cell lung cancer, head and neck cancer, breast cancer, glioma, cervical cancer, and bladder cancer. First- to third-generation EGFR inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 210 publications
(161 reference statements)
0
43
0
1
Order By: Relevance
“…Inhibiting phosphorylation of AKT1 can induce BV-2 microglia activation which leads to neuroinflammation ( Xiao et al, 2022 ). EGFR is one of the receptor proteins of the growth factor family, and participates in cell proliferation and signal transduction ( Shi et al, 2022 ). Inhibition of EGFR/MAPK signaling pathway could suppress microglia activation and reduce secondary damage related to neuroinflammation ( Qu et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting phosphorylation of AKT1 can induce BV-2 microglia activation which leads to neuroinflammation ( Xiao et al, 2022 ). EGFR is one of the receptor proteins of the growth factor family, and participates in cell proliferation and signal transduction ( Shi et al, 2022 ). Inhibition of EGFR/MAPK signaling pathway could suppress microglia activation and reduce secondary damage related to neuroinflammation ( Qu et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…These limitations are mainly due to the nature of primary and emerging secondary escape mutations in the receptor (EGFR T790M ) and acquired resistance as well as pathway mutations e.g. JAK2 V617F (EPOR/TPOR) that lead to constitutively over activation and dysregulation with detrimental outcome for patients (Chan et al, 2017; Glassman et al, 2022; Kumar et al, 2020; Shi et al, 2022).…”
Section: Mainmentioning
confidence: 99%
“…Several studies have suggested that acquired resistance mechanisms to EGFR inhibitors involve the compensatory activation of redundant signalling pathways that share effectors or downstream modulators of the EGFR signalling cascade, thus bypassing EGFR inhibition. Different pathways can serve as alternative routes for reactivation of signalling downstream of inhibited EGFR, including MET, IGF-1R, PI3K-AKT-mTOR, BRAF/RAS and Wnt signalling pathways (39)(40)(41)(42), all able to sustain cell survival, proliferation, migration, and epithelialmesenchymal transition (EMT). Therefore, we downloaded the scRNA-seq dataset published by Aissa et al ( 27) comprising 1,044 PC9 lung cells (Figure 1G) that were subject to eleven days of consecutive erlotinib treatment and sequenced at six different time points (i.e., 0, 1, 2, 4, 9, and 11 days).…”
Section: Gifcf Package Overviewmentioning
confidence: 99%